(untitled) (CIPEEX, 2022)
THE INCREASE IN CASES OF SEXUALLY TRANSMITTED INFECTIONS (STIS) HAS BEEN A MATTER OF CONCERN FOR PUBLIC HEALTH, AND IT IS IMPORTANT TO GUIDE THE POPULATION REGARDING THE FORMS OF PREVENTION AND COMPLICATIONS THAT STIS CAN BRING WHEN NOT DIAGNOSED AND TREATED. STIS THAT OCCUR DURING THE GESTATIONAL PERIOD CAN CAUSE FETAL DEATH, PRETERM BIRTH, ENCEPHALITIS, AND OTHERS. HPV INFECTION IS RESPONSIBLE FOR THE DEVELOPMENT OF CERVICAL CANCER AND HIV INFECTION LEADS TO THE DEVELOPMENT OF ACQUIRED IMMUNODEFICIENCY SYNDROME (AIDS). IN ADDITION, CURABLE STIS SUCH AS SYPHILIS, GONORRHEA, AND CHLAMYDIA FACILITATE SEXUAL TRANSMISSION OF HIV. IN THIS WAY, THE MINISTRY OF HEALTH HAS BEEN ENCOURAGING RAPID TESTS AS A STRATEGY TO INCREASE ACCESS TO DIAGNOSIS. THIS IS A CROSS-SECTIONAL DESCRIPTIVE STUDY WITH A RETROSPECTIVE APPROACH TO ANALYZE THE RESULTS OBTAINED IN THE SEROLOGICAL SCREENING OF EXTENSION ACTIONS IN THE YEARS 2017 AND 2018, OUTLINING THE EPIDEMIOLOGICAL PROFILE OF THE POSITIVE CASES. SEROLOGICAL SCREENING FOR HIV, SYPHILIS, HEPATITIS B AND C WAS CARRIED OUT AT FIVE SITES IN ANNAPOLIS, APPLYING FORMS THAT CONTAINED INFORMATION ON GENDER, RACE, MARITAL STATUS, SCHOOLING, DRUG USE, SEXUAL CHOICE, NUMBER OF SEXUAL PARTNERS, OTHERS. 481 FORMS WERE SELECTED FOR ANALYSIS WHICH CONTAINED ALL THE DATA OF THE COMPLETED FORMS AND WERE OF PARTICIPANTS OVER 18 YEARS OF AGE. THE DATA COLLECTED FROM THE FORMS WAS TYPED INTO A DATABASE IN MICROSOFT EXCEL (2016). THE RESULTS SHOWED THAT OF THE 481 FORMS ANALYZED, 63% (N = 301) WERE FEMALE AND 37% (N = 180) MALES, WITH 12 POSITIVE RESULTS (2.49%, 12/481), POSITIVE RESULTS 10 CASES OF SYPHILIS (84%, 10/12) AND 2 CASES OF HEPATITIS B (16%, 2/12), THE MAJORITY OF CASES WERE MALE, WITH A MEAN AGE OF 49 YEARS, WHITE (50%). %, 6/12), WITH COMPLETE HIGHER EDUCATION (58%, 7/12). REGARDING RISK FACTORS, MOST POSITIVE CASES REPORTED HAVING UNPROTECTED SEX (67%, 8/12) AND 42% (5/12) HAD MULTIPLE SEXUAL PARTNERS. NONE OF THE POSITIVE CASES REPORTED HAVING VISITED THE BLOOD BANK IN THE PAST 12 MONTHS AND MOST REPORTED NOT USING ANY TYPE OF DRUG (67%, 8/12) OR SHARING SYRINGES (75%, 9/12). THE ANALYSIS OF UNIVERSITY EXTENSION FORMS SHOWED US THE NEED FOR ACTIONS AIMED AT CONDUCTING RAPID TESTS IN THE POPULATION, SINCE THIS STRATEGY ALLOWS THE TRACKING OF INDIVIDUALS WITH STIS, FAVORING THE DIAGNOSIS AND EARLY TREATMENT, INTERRUPTING THE CHAIN OF TRANSMISSION OF THESE DISEASES. IN ADDITION, IT EMPHASIZES THE IMPORTANCE OF THE PHARMACIST’S ROLE IN GUIDING THE POPULATION IN RELATION TO THE PREVENTION OF STIS AND IN STIMULATING THE POPULATION TO SEEK HEALTH SERVICES EVEN WITHOUT PRESENTING SYMPTOMS.